THE PRACTICE OF REFLECTIVE PEDAGOGY IN INDONESIAN CLASSROOMS: A SYSTEMATIC REVIEW - Setyawan, Theresia Yunia (Universitas Pelita Harapan, 2022)
This was a systematic literature review study aiming at exploring the implementation of the reflective pedagogy paradigm in the Indonesian educational context. The works being reviewed in the study were gathered using Harzing’s Publish and Perish software. The criteria for including the works were being indexed by Google Scholar, published between the last ten years (2012-2021), the most cited works during their year of publication, and published in, at least, peer-reviewed journals. This review excluded conference papers published in proceedings and other works that were not published in journals. The results of the review showed that the reflective pedagogy had been widely used across subject areas and levels of education in Indonesia. It was also found out that, as the fundamental part of the pedagogy, reflection had been regarded as a process where learners looked back at their learning process to identify their experiences and the values they had learned during the process. Based on the results, this study concluded that the implementation of the reflective pedagogy could improve learners’ achievement and awareness of life values and virtues. It also recommended implementing the pedagogy to encourage learners to be autonomous in assessing their learning to prepare themselves to be lifelong learners.Bahasa Indonesia AbstrakIni adalah studi tinjauan pustaka sistematis yang bertujuan untuk mengeksplorasi implementasi paradigma pedagogi reflektif dalam konteks pendidikan Indonesia. Karya-karya yang ditinjau dalam penelitian ini dikumpulkan menggunakan perangkat lunak Harzing's Publish and Perish. Kriteria untuk memasukkan karya sedang diindeks oleh Google Scholar, diterbitkan antara sepuluh tahun terakhir (2012-2021), karya yang paling banyak dikutip selama tahun publikasi mereka, dan diterbitkan setidaknya di jurnal peer-review. Tinjauan ini mengecualikan makalah konferensi yang diterbitkan dalam prosiding dan karya lain yang tidak diterbitkan dalam jurnal. Hasil review menunjukkan bahwa pedagogi reflektif telah banyak digunakan di seluruh bidang studi dan jenjang pendidikan di Indonesia. Ditemukan juga bahwa, sebagai bagian mendasar dari pedagogi, refleksi telah dianggap sebagai proses di mana peserta didik melihat kembali proses belajar mereka untuk mengidentifikasi pengalaman mereka dan nilai-nilai yang telah mereka pelajari selama proses tersebut. Berdasarkan hasil tersebut, penelitian ini menyimpulkan bahwa penerapan pedagogi reflektif dapat meningkatkan prestasi dan kesadaran peserta didik akan nilai-nilai dan kebajikan hidup. Direkomendasikan pula penerapan pedagogi untuk mendorong peserta didik menjadi mandiri dalam menilai pembelajaran mereka untuk mempersiapkan diri menjadi pembelajar sepanjang hayat.